Investigating Equity and Social Justice Concerns in Teaching and Teacher Education : A Comprehensive Analysis - Fatima, Roohi (JOURNAL OF INDIAN EDUCATION, 2024)
This paper delves into the themes of equity and social justice within the context of teaching and teacher education in India. It contends that social justice is contingent upon the realisation of equality in diverse social settings, measured through equitable outcomes. Central to this is the acknowledgment and embracement of diversity as a manifestation of equality, and inclusion as a tangible demonstration of fairness. Within the realm of education, diversity entails recognising and valuing differences, advocating for inclusivity, and striving for equity regardless of individual distinctions. This is a research-based paper, which aims to address pertinent questions, such as the prevalent issues of social justice in India and their implications on education. It also explores the significance of equity in education and proposes strategies for integrating issues of equity and social justice into the pre-service teacher education curriculum.